The effectiveness of nifedipine/indomethacin combination therapy and nifedipine monotherapy for postponing preterm birth (25-34 weeks of gestation) in Sudanese women: a randomized clinical trial study protocol - Mohammed H. Ibrahim; Tahani Elfaki; Elhassan M. Elhassan; Somia K. Abdelrahiem; Ishag Adam (BMC, 2021)
Abstract Background Preterm birth is the most common cause of neonatal morbidity and mortality. Tocolytics are considered a standard treatment for women with threatened preterm delivery to allow time for maternal steroid administration and transfer to referral centers with neonatal intensive care units. However, there is controversy about the best tocolytic therapy to be considered as the first choice. The aim of this study is to compare the tocolytic effectiveness and tolerability of combination therapy with nifedipine and indomethacin versus nifedipine monotherapy among Sudanese women with preterm labor (PTL) as well as to compare the possible neonatal outcomes associated with each drug. Methods/design This is a randomized controlled clinical trial to be conducted in the Medani Maternity Hospital, Sudan. Women aged 18-40 years that are diagnosed with preterm labor and have a gestational age between 25 and 34 weeks will be eligible to participate in this trial. The diagnosis of threatened PTL is defined as persistent uterine contractions "(four contractions every 20 min or eight contractions every 60 min)" with cervical changes "(cervical effacement ≤80% or cervical dilatation >two cm)". Patients will be eligible regardless of the presentation of the fetus. It will be randomly decided whether participants receive nifedipine/indomethacin combination therapy or nifedipine monotherapy. The primary outcome is the number of women who do not deliver and do not need alternative tocolytic drug (terbutaline). The secondary outcome is an estimated association with neonatal morbidity and mortality. The sample size will be 117 subjects in each arm of the study, according to a type I error of 0.05 and a study power of 80%. Discussion We expect higher effectiveness of the combination indomethacin/nifedipine tocolytic therapy compared with nifedipine monotherapy. We plan to suggest this combination therapy as the best option for postponing PTL. Trial registration Clinical trial registration: PACTR202004681537890 , date of registration: March 8, 2020.